PEMBENTUKAN KELOMPOK ANTI KEKERASAN SEKSUAL ANAK (KAKSA) PADA KOMUNITAS KADER DI DESA SANUR KAJA DENPASAR - N. K., Ekawati.; Dwipayanti, N.M. Utami; Wulandari, L.P Lila (Buletin Udayana Mengabdi; Vol 10 No 2 (2011): Jurnal Udayana Mengabdi, 2012)
This Community Service was conducted in Desa Sanur Kaja on 16-17 July 2010, in the form of training and supervision on the KAKSA group members. Before the training was done, the participants were given pre-test and at the end, they were evaluated by post-test. The result showed that there is improvement of knowledge about 11.84% . Most participants felt satisfactorily toward the aspects of knowledge, skill and condition which are improved. Improvement. The evaluation result suggested that most participants stated that the training is adequate to widen the insight of KSA, KSA prevention, raising the sensitivity and curiosity to actively participate to prevent KSA. It can be suggested that the training to form the new KAKSAs can be continually done in every sub-village.